2020
DOI: 10.1002/adfm.202000852
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen‐Doped Ti3C2 MXene: Mechanism Investigation and Electrochemical Analysis

Abstract: Nitrogen doping has been proven to be a facile modification strategy to improve the electrochemical performance of 2D MXenes, a group of promising candidates for energy storage applications. However, the underlying mechanisms, especially the positions of nitrogen dopants, and its effect on the electrical properties of MXenes, are still largely unexplored. Herein, a comprehensive study is carried out to disclose the nitrogen doping mechanism in Ti 3 C 2 MXene, by employing theoretical simulation and experimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
134
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 218 publications
(137 citation statements)
references
References 55 publications
2
134
1
Order By: Relevance
“…According to DFT simulation results, nitrogen dopants locate in three possible sites in Ti 3 C 2 T x : lattice substitution (for carbon), function substitution (for ‐OH), and surface absorption (on ‐O). Moreover, electrochemical test results confirm that all the three kinds of nitrogen dopants are favorable for improving the specific capacitance of the Ti 3 C 2 electrode [97] …”
Section: Interlayer Engineering By Surface Modificationmentioning
confidence: 71%
See 1 more Smart Citation
“…According to DFT simulation results, nitrogen dopants locate in three possible sites in Ti 3 C 2 T x : lattice substitution (for carbon), function substitution (for ‐OH), and surface absorption (on ‐O). Moreover, electrochemical test results confirm that all the three kinds of nitrogen dopants are favorable for improving the specific capacitance of the Ti 3 C 2 electrode [97] …”
Section: Interlayer Engineering By Surface Modificationmentioning
confidence: 71%
“…Moreover,e lectrochemical test results confirm that all the three kinds of nitrogen dopantsa re favorable for improving the specific capacitance of the Ti 3 C 2 electrode. [97] Despite the great efforts that have been made to improve the electrocapacitive performance of MXenee lectrodes by modification of Ti 3 C 2 T x surface chemistry,t here are still many critical issues that need to be investigated. For example, how heteroatom doping will impact the electrochemical performance still needs to be further investigated.…”
Section: Surfacemodificationofmxenesvia Heteroatom Dopingmentioning
confidence: 99%
“…comprehensively studied the underlying mechanisms of nitrogen doping of 2D Ti 3 C 2 . [ 146 ] These authors found that the nitrogen dopants can be accommodated by three positions of Ti 3 C 2 including lattice substitution (LS) of C atoms, function substitution (FS) of OH groups, and surface absorption (SA) on O terminations with the calculated formation energy of −1.31, −4.71, and −2.87 eV, respectively (Figure 8c). Although the lowest formation energy is generally required to form the most stable model, it is still hard to predict which nitrogen dopant is dominant due to the different transition states of these three configurations.…”
Section: Theoretical Calculations Of Elemental Doping/substitutingmentioning
confidence: 99%
“…In order to improve the electrochemical performance of MXene-based electrodes, the most efficient method is to enhance the interlayer spacing of MXenes, and the commonly used strategy is to dope the layered MXenes with heteroatoms. [46,81] N, S, and P doping are the most extensively doping strategies, and their efficiency and feasibility have been proved for dramatically enhancing the electrochemical performance of MXenes. [21,45,57,58,[81][82][83] For example, Yoon et al [45] reported that P-doped V 2 CT x with tunable chemical compositions (3.83-4.84 at%) of P depending on the phosphorization temperature was successfully fabricated via simple heat treatment using triphenyl phosphine (TPP) as a phosphorous source in V 2 CT x .…”
Section: D Mxene Modified By Single Heteroatomsmentioning
confidence: 99%
“…[ 46,81 ] N, S, and P doping are the most extensively doping strategies, and their efficiency and feasibility have been proved for dramatically enhancing the electrochemical performance of MXenes. [ 21,45,57,58,81–83 ] For example, Yoon et al [ 45 ] reported that P‐doped V 2 CT x with tunable chemical compositions (3.83–4.84 at%) of P depending on the phosphorization temperature was successfully fabricated via simple heat treatment using triphenyl phosphine (TPP) as a phosphorous source in V 2 CT x . As shown in Figure a, the delamination of P‐doped V 2 CT x with 3.83 at% P doping after heat treated at 500 °C is displayed, indicating that the 2D structure keeps unchanged and no vanadium oxide crystals are observed.…”
Section: Synthesis Of Functional 2d Mxenesmentioning
confidence: 99%